ANALISIS PENERAPAN SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) KEUANGAN DALAM PENGELOLAAN KEUANGAN DAERAH PEMERINTAH KOTA MANADO - Pilat, Juddy Julian; Sondakh, Jullie J.; Manossoh, Hendrik (ACCOUNTABILITY, 2016)
Local autonomy gives authority to local governments to implement their own financial management, which led to public accountability through the presentation of financial statements to the public. The obligation of governments to use information technology to simplify and improve the ability of financial data processing. Implementation of an integrated Financial LMIS can facilitate financial management to produce financial information that is integrated, comprehensive, precise and accurate. The purpose of this research is to (1). analyze the supporting factors owned by Manado City Government in order to implement the Financial LMIS, (2). analyze Financial LMIS as a local financial information system in assisting the local financial management and (3). analyze internal control of Financial LMIS in financial data processing. The analytical method used is qualitative descriptive phenomenology. Qualitative data were obtained by indepth interviews, observation and documentation. Validity and reliability of the data were determined by data and resources triangulation. The acquired data were coded into patterns and analysed, data interpretation and conclusion. Results of research and analysis indicate that Manado City Government had supporting factors such in order to implement the Financial LMIS optimally such as: communication, resources, disposition/attitude and bureaucratic structures. Financial LMIS is very important and very helpful in helping an integrated local financial management as well as play a role in order to: support the organization's operations, support decision making and support the achievement of strategic goals and objectives of the organization. Financial LMIS has been supported by adequate internal controls to ensure the effectiveness and efficiency implementation of a system that has been designed with some type of control, such as: control of access and user authority, control of physical security, control of menu based functions and control of applications. Keywords: Financial Local Management Information System (LMIS), Local Financial Management.